Platelets as central hubs of inflammation - Bo, Yan; Zhao, Fei (Frontiers in Immunology, 2025)
ObjectiveTo develop the platelet inflammation hypothesis and propose the concept of platelets as the central hub regulating inflammation.MethodsWe employed a narrative review design. Based on platelets being the source of cellular fragments shed from megakaryocytes, we traced the active molecules within platelet granules to infer platelet regulatory roles in aseptic inflammation, infectious inflammation, cancer, and neuroinflammation. Furthermore, we visually mapped the central regulatory mechanisms of platelets in the aforementioned inflammatory contexts.ResultsPlatelets not only mediate hemostasis and thrombosis through the coagulation pathway but also dynamically regulate inflammatory responses through interactions between bioactive substances in platelet granules, leukocytes, vasculature, and immune signaling. This regulatory role applies across a broad spectrum of pathological inflammations. Platelets influence vascular integrity in aseptic inflammatory injury, participate in pathogen recognition and containment during infectious inflammation, and regulate immune cell recruitment and inflammatory outcomes in tumor/cancer and neuroinflammation. The central principle of platelet-mediated inflammation regulation is dual control of immune thrombogenesis through damage-associated molecular patterns (DAMPs) and pathogen-associated molecular patterns (PAMPs), thereby influencing disease outcomes.ConclusionPlatelets serve as the central hub in the microcirculatory-damaged tissue-immune inflammatory interaction network. Their immunoregulatory functions play a pivotal role in diverse inflammatory pathologies. The platelet-driven mechanism-disease-immune inflammatory regulation framework provides clinically translatable insights for diagnostic evaluation of inflammatory and thrombotic conditions, as well as for developing antiplatelet therapeutic strategies targeting diseases such as cancer and epilepsy.